The Influence of Wives’ and Husbands’ Fertility Preferences on Progression to Third Parity Births in Nepal, 1997 to 2009 - Jennings, Elyse A.; Pierotti, Rachael S. (Taylor and Francis, 2016)
As couples across the globe increasingly exercise conscious control over their reproduction, both spouses’ family-size preferences have the opportunity to influence their fertility. Using couple-level measures of rural Nepalese spouses’ family-size preferences and more than a decade of monthly panel data collected subsequently on fertility outcomes, we investigate how both spouses’ preferences influence progression to a third birth in a country where the widely professed ideal family size is two children. Contrary to expectations based on women's relative disadvantage, we find that it is wives’ preferences that drive couples’ progression to a third birth. We find also that the influence of wives’ preferences is not explained by contraceptive use but that this influence is moderated by couple communication about family planning. Wives’ preferences drive progression to a third birth among couples who had discussed how many children to have.